The Influence of Content Marketing, Perceived Quality, and Brand Trust on Repurchase Intention of Pixy Cosmetic Products in Surabaya - Setianti, Ikko Ukumi Puteri; Dermawan, Rizky (East Asian Journal of Multidisciplinary Research, 2024)
The cosmetic industry is a leading industry among the three national priority industries in Indonesia. One of the local brands that has survived in market competition until now is Pixy Cosmetic. This study examines the influence of Content Marketing, Perceived Quality, and Brand Trust on Repurchase Intention towards Pixy Cosmetic products in Surabaya. This study uses a quantitative approach and a Likert scale to measure variables. This research uses non-probability sampling with purposive sampling technique to determine the sample, using 91 respondents. Analysis technique that used in this study is SmartPLS to analyze data. The results show that Content Marketing, Perceived Quality, and Brand Trust have a positive and significant influence on Repurchase Intention towards Pixy Cosmetic products in Surabaya.